(untitled) (Journal of Economic Research & Business Administration, 2015)
The relationship between population health and economic development was theoretically proved in the paper, the diagrams were illustrated. The linear regression econometric model for estimating the effect of the population health indicators on gross domestic product per capita was proposed.